VSWR value measurement analysis using Direct Digital Synthesizer - Lorenza Louis Natalia (JAICT, 2018)
SWR Analyzer is an electronic device radio is useful to know the value of VSWR and antenna impedance without the use of radio tranciever. In this final use Direct Digital Synthesizer (DDS) to generatewaveforms analog digitally. DDS signal generation programmable via Arduino nano. The frequency used is aantenna operating frequency dipole 7 MHz which are in the range 6.9 MHz - 7.4 MHz.calibration SWR Analyzer is done by providing a form of pure resistor load with the acquisition of a data error of 4% as compared with the theory. The test results niali VSWR atantenna dipole 7 MHzusing an SWR Analyzer then compared with measuring devices in general, ie VSWR SWR meter. Earned value matching 1: 1 obtained by SWR Analyzer at a frequency of 6.9 MHz, while using the SWR meter lowest VSWR values obtained at 7:04 MHz frequency with a value ofratio matching impedance1:35: 1. The accuracy of the measurement results using the SWR Analyzer when compared with SWR meter reaches a value 83%.